Crescentia cujete L. Extract as an Substitution Alternative of Oxybenzone in Sunscreen Cream - Rahma Diyan Martha; Dara Pranidya Tilarso; Febriana Devi Nur 'Aini; Armita Regina Putri Yulindasari; Hesty Parbuntary (CHEESA: Chemical Engineering Research Articles, 2025)
The use of natural ingredients in sunscreen products is increasingly developed due to safety and eco-friendliness compared to synthetic agents. Therefore, this study aimed to evaluate the physical properties and SPF values of cream formulations containing leaf and fruit extract of Crescentia cujete L. The experimental method included cream formulation, SPF evaluation in vitro using UV-Vis spectrophotometry, and physical quality testing comprising organoleptic, homogeneity, emulsion type, spreadability, adhesion, pH, and viscosity. The results showed that formulation with leaf extract had the highest SPF value of 15.60 (medium protection category), indicating the potential of Crescentia cujete L. leaf as active ingredient in herbal-based sunscreen cream.